2020
DOI: 10.1037/pri0000118
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based relationship variables when working with affectional and gender minority clients: A systematic review.

Abstract: In this systematic review, we synthesized the quantitative and qualitative research examining the role of evidence-based relationship variables (EBRVs) in the treatment of affectional and gender minority (AGM) individuals. A comprehensive search of PsycINFO, Web of Science, and PubMed from 2009 to 2019 yielded 14 unique studies (15 articles in total). Most studies examined the role of empathy and alliance. Positive regard, strong therapeutic alliances, genuineness, and empathy were all associated with improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…All but three AWS were recruited through the NSA listserv, a non-profit organization focused on fostering an affirming environment for individuals who stutter (National Stuttering Association, 2020). It may be possible that among this sample, exposure to NSA-contingencies focused on the reinforcement of community-building behaviors and communication as opposed to decreasing dysfluencies attenuated the participants' sensitivity to aversive variables (e.g., J. M. Cohen et al, 2021;Ellis et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…All but three AWS were recruited through the NSA listserv, a non-profit organization focused on fostering an affirming environment for individuals who stutter (National Stuttering Association, 2020). It may be possible that among this sample, exposure to NSA-contingencies focused on the reinforcement of community-building behaviors and communication as opposed to decreasing dysfluencies attenuated the participants' sensitivity to aversive variables (e.g., J. M. Cohen et al, 2021;Ellis et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…In regard to gender, a recent metaanalysis suggests that it likely does not moderate dropout or outcome (Swift et al, 2019), and in one study, the majority of male and female participants indicated no gender preference for their therapist (Liddon et al, 2018). Additionally, a systematic review of evidence-based relationship variables in working with AGM individuals indicated that matching client and therapists on affectional or gender identities did not improve therapy outcomes (Ellis et al, 2020). However, there may be gender differences in preferences for the type of therapy provided.…”
Section: Therapeutic Alliance Client-therapist Matching and Psychothe...mentioning
confidence: 99%
“…Countertransference issues in therapy can be problematic if not effectively managed when working with AGM clients (Ellis et al, 2020). The literature typically examines countertransference in AGM therapy dyads in the context of case studies and is lacking in an empirical understanding of the role of transference and countertransference.…”
Section: Countertransferencementioning
confidence: 99%
“…In this regard, advocacy must occur within the therapeutic frame and therapy room but also well beyond it to create systemic change. Ellis, Meade, and Brown's (2020) article provides a systematic review of the literature published in the past 10 years focusing on the role of EBRVs in psychotherapy and medicine with AGMs yielded only 15 articles. The review revealed that empathy and positive regard were predictive of treatment engagement, and more positively rated alliance facilitated affirmative care.…”
Section: Special Issue On the Importance Of Evidence-based Relationsh...mentioning
confidence: 99%